Improvement of the model proposed by Menegotto and Pinto for steel. (1st October 2016) - Bosco, M.; Ferrara, E.; Ghersi, A.; Marino, E.M.; Rossi, P.P.
Highlights: A modified Menegotto and Pinto model for steel is proposed. The modified model improves the response in case of reloading after partial unloading. The original model is suitable for reinforced concrete structures. The original model can cause significant errors in the response of steel structures. The errors decrease when the results are averaged over a number of accelerograms. Abstract: The model proposed by Menegotto and Pinto (1973) is widely used to simulate the dynamic response of steel structures and steel bars of reinforced concrete structures. In the early 1980s, Filippou et al. (1983) improved the original model by introducing isotropic hardening and highlighted a flaw in the original formulation. Specifically, these researchers observed that if partial unloading takes place at strains lower than the maximum recorded value, the reloading path provides forces that are higher than those expected. Filippou et al. deemed that such errors were not particularly significant for reinforced concrete members and did not propose any modification to the analytical formulation of the model. In the opinion of the writers, this observation is convincing when dealing with reinforced concrete members but is questionable when referring to steel members. The abovementioned flaw is eliminated in this paper from the Menegotto and Pinto model and the improvement over the original model is shown by means of nonlinear dynamic analyses on simple reinforced concrete and steel frames.